2021
DOI: 10.3390/ijms222212309
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxidative Stress and Memantine-Incorporated Reactive Oxygen Species-Sensitive Nanoparticles on the Expression of N-Methyl-d-aspartate Receptor Subunit 1 in Brain Cancer Cells for Alzheimer’s Disease Application

Abstract: The aim of this study is to fabricate reactive oxygen species (ROS)-sensitive nanoparticles composed of succinyl β-cyclodextrin (bCDsu), memantine and thioketal linkages for application in Alzheimer’s disease, and to investigate the suppression of N-methyl-d-aspartate (NMDA) receptor 1 (NMDAR1) in cells. Thioketal diamine was attached to the carboxyl group of bCDsu to produce thioketal-decorated bCDsu conjugates (bCDsu-thioketal conjugates) and memantine was conjugated with thioketal dicarboxylic acid (memanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…36 The killing effect of Ce6-PDT on cells became stronger as the photosensitizer concentration increased, and at 8.0 g/mL, the apoptosis rate of SW260 exceeded 60%. Other studies have shown that Ce6 photodynamic therapy can treat triple-negative breast cancer, 37 brain cancer, 38 ovarian cancer, 39 and colon cancer. 40 2.3.…”
Section: Applications Of Ce6 In Photodynamic Therapymentioning
confidence: 99%
“…36 The killing effect of Ce6-PDT on cells became stronger as the photosensitizer concentration increased, and at 8.0 g/mL, the apoptosis rate of SW260 exceeded 60%. Other studies have shown that Ce6 photodynamic therapy can treat triple-negative breast cancer, 37 brain cancer, 38 ovarian cancer, 39 and colon cancer. 40 2.3.…”
Section: Applications Of Ce6 In Photodynamic Therapymentioning
confidence: 99%
“…Inhibition of iGluRs has demonstrated the ability to reduce AF incidence and alleviate AF progression in AF models using isolated rat hearts [47]. Furthermore, numerous studies have provided evidence of memantine's capacity to ameliorate oxidative damage in various diseases [48][49][50]. In human umbilical vein endothelial cells, memantine mitigated inflammation, oxidative stress, and apoptosis induced by oxidized low-density lipoprotein through the activation of the BDNF/TrkB signaling pathway [50].…”
Section: Plos Onementioning
confidence: 99%
“…Fluorescence imaging of isolated brain tissue can also measure the ability of different nano-agents to penetrate the blood–brain barrier by quantifying the fluorescence intensity of the brain [ 7 ]. The fluorescence intensity of the fluorescently Ce6-labeled bCDsu-thioketal-memantine (bCDsuMema) nanoparticles was strongest in the brain, suggesting that nanoparticles can effectively target the brain, providing a promising candidate for the inhibition of Alzheimer’s disease [ 8 ]. Alata et al [ 9 ] used in situ brain perfusion (ISPB) combined with optical brain imaging and distribution volume evaluation to determine brain accumulation of sdAbs fused to mouse Fc (sdAb-mFc) after penetration disruption of BBB.…”
Section: Optical Imaging For Assessing Intracerebral Pharmacokineticsmentioning
confidence: 99%